PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER) DAN NET PROFIT MARGIN (NPM) TERHADAP HARGA SAHAM DENGAN EARNING PER SHARE (EPS) SEBAGAI VARIABEL MODERATING - Putri Renalita Sutra Tanjung (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2021)
This research was conducted with aims to know the effect of current ratio, debt to equity ratio and net profit margin on share price with earning per share as a moderating variable. The object of this research is the consumer goods industry sector listed on the Indonesian Stock Exchange in 2017- 2019. The samples obtained were 126 samples from 42 companies for 3 years. Determination of the sample using a purposive sampling method. Research conducted with quantitive-descriptive approach, and the analytical technique used to analyze the data was Moderated Regression Analysis (MRA). The result of this research indicate that simultaneously all the variables used in this research which is CR, DER, NPM and all moderates has a significant effect on share price. While partially CR has a significant negative effect on share prices, DER and NPM have no effect on share prices, and EPS can moderate the effect of CR, DER, and NPM on share prices. Keywords: CR, DER, NPM and EPS.